SMART GARDEN SYSTEM SEBAGAI PENGENDALI DAN PEMANTAU RUANG GREENHOUSE BERBASIS INTERNET OF THINGS (IOT) - Alberto Leo Agung; Widodo, Bambang; Stepanus (Prodi Teknik Elektro FT UKI, 2024)
Rapid technological advances, especially in technology based on the Internet of Things (IoT). The Internet of Things creates a smart environment that provides intelligence in various fields, one of which is agriculture and plantations. Gardening activities are activities to cultivate or plant plants on an empty land or a planting medium. Gardening begins with planting plants, monitoring plant growth and caring for them by watering and fertilizing so plants can thrive. Use of Internet of Things (IoT) based technology to help promote plant growth. This research is focused on controlling and monitoring plants by using a planting medium, namely greenhouse. This control and monitoring is carried out by using an application that is connected to the internet connection which will then be stored in a database from the firebase platform. The application is made on a Mit App Inventor platform and installed on an Android device where the application is named IoTMonitoring which can assist in controlling and monitoring by taking into account the ideal values ​​needed by plants. Based on the results of monitoring carried out with the lowest conditions for temperatures reaching temperatures reaching 23.40C, air humidity 44.7%, soil moisture 543%, and light intensity 0 lumens. At the highest conditions for temperature reaching 38.3 0C, air humidity 82.7%, soil moisture 730%, and light intensity 15263 lumens obtained from the readings of the sensor values ​​in the greenhouse room. Meanwhile, the control is carried out by watering plants before 09.00 to maintain soil moisture and if the humidity is below the ideal value, for temperature and humidity the exhaust fan is in the ON position if the temperature is above 320C and the humidity is below 55%. And for grow lights are in the ON status if the light is below 30 lumens. Keywords: Internet of Things, Tanaman, Greenhouse, Android, Firebase, Mit App Inventor.